2018
DOI: 10.31616/asj.2018.12.4.691
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Short-Form 36 Scores and Neck Disability Index in Patients Undergoing Anterior Cervical Discectomy and Fusion

Abstract: Study DesignCase control study.PurposeTo determine how the Neck Disability Index (NDI), a cervical spine-specific outcome, reflects health-related quality-of-life, and if NDI is correlated to the 36-item Short-Form Health Survey (SF-36) scores.Overview of LiteratureNDI is a useful tool for assessing health-related quality of life in patients with neck pain.MethodsWe used the Pearson product-moment correlation coefficient to assess the validity of all items under NDI and SF-36, and the Pearson’s correlation coe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…This, as well as the fact that NDI has been shown to sufficiently evaluate and represent a patient’s physical and mental quality of life, suggests that fusion status alone may not be a significant predictor of successful outcome. 24 Although our small sample sizes are small, we believe the rigorous patient selection, data collection, and postoperative follow-up monitoring afforded by the clinical trial creates high-quality data. Because the sample sizes were small, we avoid ascribing statistical significance to our findings and instead focus on descriptive reporting our experience with delayed union in ACDF due to the paucity of data available to clinicians for decision making in this difficult scenario.…”
Section: Discussionmentioning
confidence: 99%
“…This, as well as the fact that NDI has been shown to sufficiently evaluate and represent a patient’s physical and mental quality of life, suggests that fusion status alone may not be a significant predictor of successful outcome. 24 Although our small sample sizes are small, we believe the rigorous patient selection, data collection, and postoperative follow-up monitoring afforded by the clinical trial creates high-quality data. Because the sample sizes were small, we avoid ascribing statistical significance to our findings and instead focus on descriptive reporting our experience with delayed union in ACDF due to the paucity of data available to clinicians for decision making in this difficult scenario.…”
Section: Discussionmentioning
confidence: 99%
“…Although less common in the literature, direct correlation studies have reported similar results regarding both the significance and strength of relationship between neck disability and mental health PROMs. Specifically, both lumbar and cervical spine studies have evaluated the correlation of disability with Patient-Reported Outcomes Measurement Information System (PROMIS) metrics, 14,22 EuroQol-5D, 23 SF-36 MCS, 23,24 and HADS. 23 Although Purvis et al 22 conducted their study among lumbar spine patients, the authors were able to establish a strong correlation between PROMIS depression/anxiety and ODI.…”
Section: Discussionmentioning
confidence: 99%
“…While the improvement in PCS from baseline to 24 months was not statistically significant between ACDF and M6-C, the significantly higher PCS score at 24 months for M6-C vs ACDF could have been due to the significantly higher baseline PCS score for M6-C vs ACDF. This difference could potentially have influenced the NDI and thus the CCS as studies have shown a correlation between NDI and the PCS of the SF-36 [31]. However, the PS model did include NDI thus negating the PCS discrepancy and its potential influence on the CCS.…”
Section: Discussionmentioning
confidence: 99%